2019
DOI: 10.1039/c9ra04391h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different dispersants on rheological behaviors of coal water slurry prepared from a low quality coal

Abstract: To improve the efficiency of the gasification or combustion process of coal water slurry (CWS), it is significant to optimize the rheological properties and increase the solid concentration of CWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Hu et al reported that the maximum solid loading of CWS prepared from two upgraded coals based on flotation method was about 6% higher than that prepared from the raw low‐quality coals, which could be attributed to the apparent decrement of specific surface area and porosity after flotation 17 . Identical results were obtained by Hu et al, and the improvement of slurryability of the refined coal was found to be related to the decrease in both the porosity and hydrophilicity of coal particles 18 . Zou et al observed the maximum solid loadings to decrease by 4.6%, 6.6%, and 4.4%, respectively, for acid–alkali leaching of Hebi coal, Huainan coal, and Jingyuan coal at 170°C to 180°C, which was due to the changes of organic matrix and surface properties 19 .…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Hu et al reported that the maximum solid loading of CWS prepared from two upgraded coals based on flotation method was about 6% higher than that prepared from the raw low‐quality coals, which could be attributed to the apparent decrement of specific surface area and porosity after flotation 17 . Identical results were obtained by Hu et al, and the improvement of slurryability of the refined coal was found to be related to the decrease in both the porosity and hydrophilicity of coal particles 18 . Zou et al observed the maximum solid loadings to decrease by 4.6%, 6.6%, and 4.4%, respectively, for acid–alkali leaching of Hebi coal, Huainan coal, and Jingyuan coal at 170°C to 180°C, which was due to the changes of organic matrix and surface properties 19 .…”
Section: Introductionmentioning
confidence: 82%
“…The relationship between the properties of CWS and mineral matters was accidentally mentioned by some researchers, [13][14][15][16][17][18][19][20] but the underlying mechanism was not studied in depth. Pittsburgh No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 A high-quality CWS should exhibit a high solid content and low viscosity; the additives used are vitally important in this regard. 3 At present, the anionic additives used in industrial applications include naphthalenesulfonates, aliphatic sulfonates, lignin sulfonates, humate sulfonates, and carboxylate. 4 7 …”
Section: Introductionmentioning
confidence: 99%
“…Eight projects at various stages of implementation are underway in China, all of which are intended to replace traditional fuels completely. In general, in Nigeria, Qatar, Malaysia, and the United States, about 50 facilities with a total capacity of more than 300 million tons of fuel per year are at the design and construction stage [4]. Japan, India [5], Poland, Indonesia, Pakistan joined the problem.…”
Section: Introductionmentioning
confidence: 99%